2015
DOI: 10.1039/c5ra09668e
|View full text |Cite
|
Sign up to set email alerts
|

Effective increase in the refractive index of novel transparent silicone hybrid films by introduction of functionalized silicon nanoparticles

Abstract: The refractive index of novel transparent silicone hybrid films can be effectively enhanced by introduction of functionalized silicon nanoparticles via a facile strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In addition, such stability remained when the surface was set aside without special protection for at least three months (see Figure c), indicating that the surface possesses good durability. Furthermore, by employing a pencil hardness test, the EMS layer possessed a pencil hardness of 2H, indicating a reasonable hardness in abrasion resistance. , …”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, such stability remained when the surface was set aside without special protection for at least three months (see Figure c), indicating that the surface possesses good durability. Furthermore, by employing a pencil hardness test, the EMS layer possessed a pencil hardness of 2H, indicating a reasonable hardness in abrasion resistance. , …”
Section: Results and Discussionmentioning
confidence: 98%
“…Furthermore, by employing a pencil hardness test, the EMS layer possessed a pencil hardness of 2H, indicating a reasonable hardness in abrasion resistance. 58,59 It has been demonstrated that a sticky superhydrophobic surface has great advantages in many industrial applications, such as microsample analysis, 17,18,60 and droplet-based microreactors. 23,61−63 The key techniques of these applications are based on the effectiveness of transporting a droplet from one surface to another.…”
Section: Resultsmentioning
confidence: 99%
“…Large amounts of sulfonates and dispersants were added to the formulations, and they were less resistant to acidity and salt. The increase in the content of silicone surfactants in the condensate demulsifier increases the silicon content of the condensate, thereby reducing the condensate quality [17,18]. In addition, the demulsifier formulations have variable and complex components, and generally have poor stability [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the maximum of refractive index is limited to 1.54–1.60, which is far from the requirements of rapidly developing technologies . Incorporation of inorganic materials with relative higher refractive index (TiO 2 , ZnO, ZnS, graphene nanoparticles, and Si) into an organic matrix is capable of enlarging the optical parameters to a great extent, generally up to a value of 2.5–3.0, which offers more chances for the fabrication of novel ordered micro/nanostructures. Photonic crystals (PCs), for example, regularly arrange materials of high and low dielectric constants on the order of the wavelength of light.…”
Section: Introductionmentioning
confidence: 99%